2007
DOI: 10.5194/acp-7-511-2007
|View full text |Cite
|
Sign up to set email alerts
|

Arctic smoke – record high air pollution levels in the European Arctic due to agricultural fires in Eastern Europe in spring 2006

Abstract: Abstract. In spring 2006, the European Arctic was abnormally warm, setting new historical temperature records. During this warm period, smoke from agricultural fires in Eastern Europe intruded into the European Arctic and caused the most severe air pollution episodes ever recorded there. This paper confirms that biomass burning (BB) was indeed the source of the observed air pollution, studies the transport of the smoke into the Arctic, and presents an overview of the observations taken during the episode. Fire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
334
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(355 citation statements)
references
References 79 publications
(73 reference statements)
17
334
1
3
Order By: Relevance
“…However, this central Asian source was found to be a smaller contributor of total Arctic BC than eastern Asia. Similarly, Hirdman et al (2010) and Stohl et al (2007) also identified a primarily northeastern Eurasian source to Arctic BC in the winter-late spring. The lack of a distinct eastern Asian source for Factor 3, BC, may indicate that the 10-day trajectory analysis was not long enough to fully capture this influence.…”
Section: K M Macdonald Et Al: Temporally Delineated Sources Of Majmentioning
confidence: 99%
“…However, this central Asian source was found to be a smaller contributor of total Arctic BC than eastern Asia. Similarly, Hirdman et al (2010) and Stohl et al (2007) also identified a primarily northeastern Eurasian source to Arctic BC in the winter-late spring. The lack of a distinct eastern Asian source for Factor 3, BC, may indicate that the 10-day trajectory analysis was not long enough to fully capture this influence.…”
Section: K M Macdonald Et Al: Temporally Delineated Sources Of Majmentioning
confidence: 99%
“…and has also been linked with heavy smog and haze episodes (e.g. Mukai et al, 2015;Stohl et al, 2007).…”
Section: Gas Flaringmentioning
confidence: 99%
“…This makes it impossible to create one atmospheric LUT, which would represent aerosol properties well on global scale. As current work is dedicated to AOT retrieval in Arctic region, we took the advantage of ground based aerosol measurements and created a LUT using phase function and single scattering albedo values measured in situ during one of the regular pollution events in Arctic Stohl et al, 2007) . The AOT range was from 0 to 1 (at 500 nm).…”
Section: Calculation Of Luts For Arctic Conditionsmentioning
confidence: 99%